KONFLIK MAHASISWA TIMUR DI KOTA MALANG (Studi Kasus pada Mahasiswa Timur di Kota Malang) - Kresna Abdi Parela; Winin Maulidya Saffanah; Khoirul Anwar (Sosioglobal, 2018)
Intergroup conflict is something that often occur in society. Differences of identity and values adopted could occurence the clash between two group that exist in society. This thing is also happen in students from different origins in Malang. This research is focusing in students from East Indonesia since they often involved in the friction both with fellow student groups or with  communities near their neighborhood. Spesifically, this study will discuss about effect dan see it through the roots of this conflict. The enviromental diffirences experienced by students from Eastern Indonesia and their close relationships with friends from the same region make them a solid group especially when there is conflict with other groups. This research uses qualitative approach and informan is chosen by snow ball sampling. Data from this research is collected through observation, interview, and documentation. Data obtained from students will be elaborated with various documents obtained from both media and police.Based on these various data then would be seen cause of the occurrence of conflicts and solutions that have been done in overcoming the problem. Keywords: Conflict Map, Conflict, Student, East indonesia